A Review and Criticism of Virtuous Life in the Secular Age - Mokhtar Nouri; Ghodrat Ahmadian (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Virtuous Life in the Secular Age is the work of the Iranian thinker Farhang Rajaee and the Canadian philosopher Charles Taylor. This book is written based on a common concern between the two thinkers. This common concern is the relationship between "religion and modernity" and the possibility of a religious life in the modern world. The book is a combination of authorship and translation and written in the Framework of Thomas Springs. In the present article, while introducing and reviewing the mentioned work, its critique and critical evaluation will be on the author’s agenda. Criticism of the work indicates that methodologically the work has not been able to implement the four stages of Springs. Therefore, the most important critique of the present work can be considered a "methodological" critique.